Permissive Bankruptcy Abstention - Susan Block-Lieb (Washington University Law Quarterly, 1998)
Parts I and II of this Article provide background discussions. Part I discusses the abstention doctrines applied outside the bankruptcy context. Part II describes the doctrines governing abstention from bankruptcy jurisdiction. Because the development of the bankruptcy abstention doctrines is complicated, Part II proceeds chronologically, beginning with the Supreme Court's decision in Thompson v. Magnolia Petroleum Co., and concluding with a discussion of case law interpreting the current permissive bankruptcy abstention provision, 28 U.S.C. § 1334(c)(1), which was enacted with the 1984 amendments to the Bankruptcy Code. Relying on this background material, Part III contends that section 1334(c)(1) should be construed to incorporate both the bankruptcy and non-bankruptcy abstention doctrines. Parts IV, V and VI consider the contours of bankruptcy abstention in light of the institutional and qualitative differences between bankruptcy jurisdiction and other grants of federal jurisdiction. Part IV focuses on the constitutional distinctions between the judicial authority of non-Article III bankruptcy courts and Article III district courts, and concludes that there is no constitutional basis for the substantially distinct grounds for abstention from bankruptcy jurisdiction and from other grants of federal jurisdiction. Part V considers whether the scope of the permissive bankruptcy abstention provision should differ depending upon whether arising in and related to proceedings are best characterized as a form of federal question or supplemental jurisdiction. It contends that, no matter how bankruptcy jurisdiction over proceedings arising under state law is categorized, questions regarding the scope of section 1334(c)(1) are questions of statutory construction. Read as such, the permissive bankruptcy abstention provision should not be construed to adopt distinct standards for abstention from different sorts of bankruptcy proceedings. Part VI turns to the functional purposes of the broad grant of bankruptcy jurisdiction-the expeditious resolution of bankruptcy cases. Although Congress generally understood the consolidation of all bankruptcy jurisdiction in a single federal forum as the best means of accomplishing this bankruptcy goal of expeditiousness, there may be circumstances in which efficiency in administration is better accomplished through a delegation of judicial duties. Only in these limited circumstances, however, should the functional distinction between bankruptcy and district courts justify a broader abstention doctrine.
Keywords: Bankruptcy; Abstention doctrine (Law); Ancillary jurisdiction; Bankruptcy law; Federal jurisdiction